Armoede en sociale uitsluiting jaarboek 2021 - Coene, Jill; Ghys, Tuur; Hubeau, Bernard; Marchal, Sarah; Raeymaeckers, Peter; Remmen, Roy (ASP editions - Academic and Scientific Publishers, 2021)
In this 30th edition of the Yearbook on Poverty and Social Exclusion, we look back on 30 years of fighting poverty. How have the poverty figures evolved? We take a closer look at access to justice, education and housing. Next, we are looking for an answer to the question of what constitutes a structural poverty policy. Can the law be of any significance here? This year's theme section is dedicated to the coronapandemic and its link to poverty. Subsequently, a number of civil society organisations are given a chance to express their expertise and findings. In a final section, the Yearbook presents an overview of figures on poverty and social exclusion.